Library Impact Practice Brief: Supporting Bibliometric Data Needs at Academic Institutions. - Gordon, Shannon; Hitchens, Alison (Association of Research Libraries, 2020)
This practice brief presents research conducted by staff at the University of Waterloo Library as part of the library’s participation in ARL’s Research Library Impact Framework initiative. The research addressed the question, “How can research libraries support their campus community in accessing needed bibliometric data for institutional-level purposes?” The brief explores: service background, partners, service providers and users, how bibliometric data are used, data sources, key lessons learned, and recommended resources
Keywords: bibliometrics; library services; research impact